PEMBUATAN PUPUK ORGANIK BERBAHAN BAKU SAMPAH DI KOTA PROBOLINGGO - Wahyono, Sri (BPPT)
Like other Cities in Indonesia, Kota Probolinggo also faces municipal solid waste problems. To overcome it, Kota Probolinggo is trying to do activity of garbage recycle at household scale and also in neighbour scale. One of the efforts is converting it to become organic fertilizer with a good quality, a real fertilizer required by the farmers to improve soil fertility which becoming decreases. To support the activity, in year budget 2008/2009, Pusat Teknologi Lingkungan - BPPT has done a disemination technology of Accelerated Revolver Windrow Composting (ARWC) for optimization of composting which have been done in Kota Probolinggo. Technology ARWC was developed by BPPT which has been checked and tested. Technology ARWC is fermentation system of organic garbage done aerobically by the way of heaped (windrow) and revolved regularly, turns into stable matter like humus in accelerated time. The product is compost, either in the form of ordinary compost and also compost granule, with a good quality and fulfi lls national standard. Processing activity of garbage becomes organic fertilizer has opened new employment and increases management system effi ciency and lengthens TPA age.Key Words: Municipal solid waste, Composting